A New Educational Movement in Integrated Islamic Schools - Dewi Suriyani Djamdjuri; Asri Rohmah (ENGLISH, 2014)
In the world of education, Islamic School has become the most important concern for Muslim. The main objective of this study is to know that Islamic Integrated Schools in Indonesia are mostly keen to obtain knowledge from both religious subjects and modern subjects. The purpose of this study is to determine how is the students and graduation of Integrated Islamic Schools in the facing the world in the future but remains the basis of Islam. The data were analyzed from the books related with Muslim education and website of some Islamic articles in the form of Discourse Analysis.